(untitled) (International Journal of Nursing Education, 2022)
Introduction: In adolescent girls, the need for iron increases due to accelerated growth and monthly iron loss because of menstruation. Anemia in adolescent girls can cause a decrease in learning concentration, headaches, dizziness, drowsiness, weakness, pale skin, and others. This study aimed to determine the effectiveness of the anemia prevention education program on adolescent girls’ knowledge, attitudes, and practices in Indonesian rural areas. Method: The research sample consisted of 81 respondents (40 in the control group and 41 in the intervention group) from two schools, who were selected using total sampling for the control group and quota sampling for the intervention group. The anemia prevention education intervention consisted of 4 meeting sessions held every week for a month with 30-40 minutes for each meeting. Result: Data analysis revealed that the anemia prevention education program effectively increased anemia knowledge (p=0.00) and practice (p=0.02). However, this program was ineffective in changing adolescent girls’ attitudes about anemia prevention (p=1.00) because adolescent girls had a positive attitude (100%) both before and after receiving education. Conclusion: As a result, it can be stated that nurses and other health workers can apply for the anemia prevention education program conducted by the Public Health Center to improve adolescent girls’ knowledge and practice of anemia prevention.